2021
DOI: 10.1007/978-3-030-86800-0_40
|View full text |Cite
|
Sign up to set email alerts
|

Obsolescence in IT Work: Causes, Consequences and Counter-Measures

Abstract: The fast-moving nature of information technology is causing frequent obsolescence of technologies and competences. Changes in the environment cause a reduction in the need and demand of old competences. This results in a depreciation of these old competences and a reduction in performance in comparison to individuals with up-to-date competences. Obsolescence is especially relevant for IT professionals because the technologies they work with, and thus the demanded competences, change particularly frequently. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
(119 reference statements)
0
3
0
Order By: Relevance
“…Given the increasing role of freelance developers in digital transformation [25][26][27][28][29]39], their insights are invaluable to the broader community. Simultaneously, the results provide information about freelancers and their work, such as the importance of the adequate projects' selection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the increasing role of freelance developers in digital transformation [25][26][27][28][29]39], their insights are invaluable to the broader community. Simultaneously, the results provide information about freelancers and their work, such as the importance of the adequate projects' selection.…”
Section: Discussionmentioning
confidence: 99%
“…Freelance developers, while integral to the IT industry, face numerous specific challenges such as inconsistent income, reliance on past clients' reviews, variable competition, evolving skill requirements, and dependency on freelancing platforms [28,29]. ey are oen the first to be affected by shis in trends and hypes [29], yet they play a pivotal role in the global delivery of IT development services and digital transformation [25,26]. Existing research on freelancers in IT tends to take a broad approach, oen overlooking the specific activities or project types these professionals engage in [26].…”
Section: Freelance Developersmentioning
confidence: 99%
“…We found seven articles that to varying degrees, touch on socio‐technical issues in the gig economy, although four do so without labeling them as such. Gussek and Wiesche's (2022) review clarifies the “the forms and tasks of work in the gig economy” and calls for more research into crowdsourcing; they speculate that “the gig platform as a technology could become more autonomous and accordingly also take on a role as an actor in its own regard” (p. 12). Similarly, Stocker et al (2021) review literature on platform economics and regulation and discuss characteristics of the gig economy including trust and information asymmetries, reputation and rating systems, safety and security, and power.…”
Section: Related Workmentioning
confidence: 99%
“…The high financial, environmental, and human costs of mistakes in some sectors or the reduced supply of highly skilled labor induce employers to pay for training (Sampson & Tang, 2016). Gussek et al (2021) showed that training is a primary measure to prevent skills obsolescence due to technological changes. However, due to financial considerations, organizations are more willing to train their younger employees in new technologies than their experienced employees.…”
Section: Industry-level Factorsmentioning
confidence: 99%
“…The search in the two databases did not produce a similar study that provides a multidimensional comprehensive analysis of the determinants of employer-provided training. Some reviews and meta-analyzes address specific aspects of learning and training in organizations, e.g., conceptualization of training (Cerasoli et al, 2018), talent development and talent management (Kaliannan et al, 2023;Rowe, 2019), the impact of skills obsolescence on training (Gussek et al, 2021) and the role of technological change, particularly the fourth industrial revolution (Aranda Jiménez et al, 2022;Verma & Venkatesan, 2021). Thus, the main contribution of this article to the current state of research in this area is that it presents the latest evidence regarding companies' investments in adult learning.…”
Section: Introductionmentioning
confidence: 99%